Analysis of Students' Difficulties in Distance Materials in Space Based on Anderson's Knowledge Dimension - Laela Nur Rokhmawati; Nani Ratnaningsih (Universitas Negeri Makassar, 2021)
This study analyzes the difficulties of students in the distance material in space based on the dimensions of Anderson's knowledge in class XII.IPA SMA Negeri 2 Banjar in the academic year 2021/2022. The purpose of this study was to determine the difficulties of students in the distance material in space based on the dimensions of Anderson's knowledge. The background of the research is that learning on distance material in class XII.IPA SMA Negeri 2 Banjar has not achieved the learning objectives. Students have difficulty understanding the material. The research subjects were 9 students from class XII.IPA SMA Negeri 2 Banjar for the academic year 2021/2022. Subject selection was based on a purposive sampling technique selected based on different academic abilities (high, medium, and low) and able to communicate verbally well. The method used in this research is descriptive qualitative with written test and interview techniques. The result of this research is that there are difficulties in each group of students who have different academic abilities.